Geochemistry of the (meta-)mafic rocks from the Gonzalito mining district, northern Patagonia - Martínez Dopico, Carmen Irene (2020)
In spite of hosting one of the most important Pb–Ag–Zn mineralizations in Patagonia, the metamorphic history of the rocks of the Mina Gonzalito Complex (MGC; east of the North Patagonian Massif) is still unclear. The complex consists of schists, para- and ortho-derived gneisses, ranging from greenschist to amphibolite facies, and metamafic rocks. Leucogranites and pegmatites were intruded synkinematically. Field, petrological and thermochronological evidence indicates that the MGC experienced an early prograde path and metamorphic peak during the Early Ordovician (ca. 472 Ma), magmatism and localized post-peak deformation and re-equilibrium at lower pressure, followed by uplift during the Late Permian. The MGC is intruded by the calc-alkaline Santa Rosa Diorite (SiO2 = 58.7–60.4 wt%; LaN/YbN = 7.2–10.5) and trachyte dike swarms in the Late Permian- Early Triassic. The mafic intrusives of the MGC form small schistose, massive and banded bodies interlayered within the gneisses and granites and recorded recrystallization of hornblende + plagioclase + quartz + titanite ± clinopyroxene ± biotite ± ilmenite. The metamafic rocks are mostly tholeiitic gabbros having SiO2 (45.4–52.1 wt%), TiO2 (0.62–2.88 wt%), flat REE patterns (LaN/YbN = 0.48–2.76), although some pyroxene-banded varieties show higher ratios. Initial P–T modelling in the NCKFMASHTO system for the metamafic rocks defined P-T conditions between 550 and 730 °C and 1–4 kbar. Our data suggest that the protolith of the metamafic rocks was emplaced in a shallow environment, associated with underplating of mantle-derived magmas slightly modified by crustal contamination. The intrusion of mantle-derived magmas may have been related either to a magmatic arc or to a continental rift environment. The model involving an Ordovician intracontinental back-arc basin is favored herein because it can reasonably explain many other geological features of Early Paleozoic basement rocks from northern Patagonia.